Progress in behavior modification. - Hersen, Michel; Eisler, Richard M.; Miller, Peter M. (Peter Michael), 1942- (Academic Press, 1981)
Progress in Behavior Modification, Volume 12 covers the developments in the study of behavior modification. The book presents papers on the appraisal of research and a proposal for an integrative model for agoraphobia; on organizational behavior management; and on behavioral techniques for decreasing aberrant behaviors of retarded and autistic persons. The text also includes papers on behavior therapy in rehabilitation; competence, depression, and behavior modification with women; and on the theory, research, and practice in self-control procedures with the mentally retarded. A paper on the mo.